Trade policy, income risk, and welfare - Tom Krebs; Pravin Krishna; William Maloney (Brown University, Department of Economics, 2004)
This paper studies empirically the relationship between trade policy and individual income risk faced by workers. The analysis proceeds in three steps. First, longitudinal data on workers are used to estimate time-varying individual income risk parameters in various manufacturing sectors. The estimated income risk parameters and data on trade barriers are then used to analyze the relationship between trade policy and income risk. Finally, a simple dynamic general equilibrium model with incomplete markets is used assess the corresponding welfare costs. In the implementation of this methodology using Mexican data, we find that trade policy changes have a significant short run effect on income risk. Further, while the tariff level has an insignificant mean effect, it nevertheless changes the degree to which macroeconomic shocks affect income risk.
Keywords: D52; E21; F1; F13; 330; Trade Policy; Income Risk; Macroeconomics; Außenhandelspolitik; Einkommen; Risiko; Verarbeitendes Gewerbe; Dynamisches Gleichgewicht; Schätzung; Mexiko